2010
DOI: 10.2528/pierl09110605
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low Intensity Coherent Electromagnetic Millimeter Radiation (Emr) on Aqua Solution of Dna

Abstract: Abstract-The thermostability and density of water-salt solutions of DNA, irradiated by non thermal coherent millimeter electromagnetic waves with frequency 64.5 GHz have been investigated using the methods of spectrophotometry and densitometry. It is shown that the thermostability of DNA and density of its solutions are increased, depending on time of irradiation. It is expected that under the influence of millimeter electromagnetic radiation the hydration of DNA and ions of Na + that are present in solution d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Wheat Seedling Shoots works as well (Babayan et al, 2006;Betskii et al, 2004;Devyatkov et al, 1991;Kalantaryan et al, 2010), since it may be assumed the mentioned frequencies of EMI effect on DNA structure. It may be also assumed that the decreasing of number of fractions in peroxidase isoenzyme spectrum indicate that organism overcomes stress state.…”
Section: Nerkararyan Et Al Effect Of Millimeter Waves With Low Intenmentioning
confidence: 99%
See 2 more Smart Citations
“…Wheat Seedling Shoots works as well (Babayan et al, 2006;Betskii et al, 2004;Devyatkov et al, 1991;Kalantaryan et al, 2010), since it may be assumed the mentioned frequencies of EMI effect on DNA structure. It may be also assumed that the decreasing of number of fractions in peroxidase isoenzyme spectrum indicate that organism overcomes stress state.…”
Section: Nerkararyan Et Al Effect Of Millimeter Waves With Low Intenmentioning
confidence: 99%
“…This fact corresponds to data of investigations devoted to EMI EHF effect on DNA structure (Babayan et al, 2006;Kalantaryan et al, 2010). …”
Section: Nerkararyan Et Al Effect Of Millimeter Waves With Low Intenmentioning
confidence: 99%
See 1 more Smart Citation
“…EMI from different artificial sources irradiating in different frequency diapasons has a pronounced effect on living organisms. Nowadays it has been shown that EMI with extremely high frequencies (EHF) may influence practically all known types of cells in systems of arbitrary organization level of living material (Babayan et al, 2006;Kalantaryan et al, 2010;Vardevanyan et al, 2013). Thus, it has been revealed that EMI EHF in frequency diapason of 41.6-42.0 GHz results in yeast growth rate changing in logarithmic phase (Grundler and Kaiser, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]. According to literature, the millimeter-wave therapy increases the level of immune resistance, influences different stages of pathogenesis, changes enzymatic reaction activity and growth rate, destroys microorganisms, and increases the thermostability of DNA [4][5][6]. The literature has shown that millimeter waves have strong effect on the process and bioelectric activity of neurochemical functions of the brain, increase the cortical tension, and influence the spike activity of neurons in the supraoptic nucleus of the hypothalamus in rats [7,8].…”
Section: Introductionmentioning
confidence: 99%